Novel Extract from Beetle Ulomoides dermestoides: A Study of Composition and Antioxidant Activity - Nina A. Ushakova; Efim S. Brodsky; Olga V. Tikhonova; Alexander E. Dontsov; Maria V. Marsova; Andrey A. Shelepchikov; Alexander I. Bastrakov (MDPI AG, 2021)
A biologically active extract from the darkling beetle Ulomoides dermestoides was obtained using the electro-pulse plasma dynamic extraction method. The beetle water extract contained a complex of antioxidant substances such as antioxidant enzymes and nonprotein antioxidants, as well as a complex of heat shock antistress proteins. This determines the rather high antioxidant activity of the aqueous extract of the beetle, i.e., 1 mg of dry matter/mL of the extract has an equivalent antioxidant activity to 0.2 mM Trolox (a water-soluble analog of vitamin E). It was shown that the beetle extract can lead to a 25-30% increase in the average lifespan of nematode Caenorhabditiselegans, under normal conditions, and a 12-17% increase under conditions of oxidative stress (with paraquat), and significantly inhibits the fructosylation reaction of serum albumin. Therefore, the beetle aqueous extract shows promise as a biologically active complex exhibiting antioxidant activity.